2021
DOI: 10.1007/s40670-021-01364-1
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Health Science Students’ Preparedness and Perception of Interactive Virtual Laboratory Simulation

Abstract: The achievement of learning goals via laboratory practical depends on both extrinsic and intrinsic factors. They could be limited by laboratory time, incurred cost, safety, self-efficacy, inadequate prior preparation by learners, and different learning styles. Hence, virtual laboratory simulation (vLAB) may be an appropriate e-learning tool to overcome these restrictions. In this study, student’s perception of the usefulness of vLAB was determined by using deoxyribonucleic acid (DNA) gel electrophoresis and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…The majority of past studies investigated the e-learning technologies for general purposes, either as a complementary method (substituting selected parts of teaching and learning activities with online learning or blended learning) or as the main method (full online learning) [ 52 – 54 , 60 , 62 , 64 , 65 , 67 , 69 , 72 ]. A small number of advanced technologies were available, such as virtual reality [ 59 , 63 , 68 , 70 ] and telesimulation [ 71 ]. Technologies such as Kahoot!™ and GaMed©™ were used to complement (e.g., enhance motivation and engagement) teaching and learning activities [ 56 , 57 , 61 ], or EHRNE software was used to mimic the real clinical practice of online health documentation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of past studies investigated the e-learning technologies for general purposes, either as a complementary method (substituting selected parts of teaching and learning activities with online learning or blended learning) or as the main method (full online learning) [ 52 – 54 , 60 , 62 , 64 , 65 , 67 , 69 , 72 ]. A small number of advanced technologies were available, such as virtual reality [ 59 , 63 , 68 , 70 ] and telesimulation [ 71 ]. Technologies such as Kahoot!™ and GaMed©™ were used to complement (e.g., enhance motivation and engagement) teaching and learning activities [ 56 , 57 , 61 ], or EHRNE software was used to mimic the real clinical practice of online health documentation [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the COVID-19 studies explored the learners’ experiences on how technology becomes a part of daily life, focusing on life experiences rather than on technology. It can be summarized where the pre-COVID studies observed consumer and design studies on the use of technology [ 54 – 66 ], except for some [ 52 , 53 ], whereas COVID-19 studies observed life experience as learners utilizing technology in learning [ 67 , 69 , 71 , 72 , 74 ], except for some [ 68 , 70 , 73 ]. Studies focusing on the technology and product emphasized their advantages and were optimistically reported, whereas studies on life experience paid more attention to reporting on the challenges and limitations in learning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 Youmans presented an interesting report on how unique it is to teach during the COVID-19 pandemic in terms of other distance learning experiences. 21 There are many case studies on distance learning experiences in various fields of both basic and applied sciences (e.g., physics, 22 computational chemistry, 23 theoretical analysis, 24 biochemistry, 25 microbiology, 26 health, 27 mechanics 28 ). Furthermore, comparative studies have been widely conducted.…”
Section: Introductionmentioning
confidence: 99%